The antioxidant α-lipoic acid attenuates intermittent hypoxia-related renal injury in a mouse model of sleep apnea. Issue 6 (18th March 2019) - Abuyassin, Bisher; Badran, Mohammad; Ayas, Najib T; Laher, Ismail
Abstract: Study Objectives: Oxidative stress and inflammation are proposed to mediate kidney diseases that occur in patients with obstructive sleep apnea (OSA). We examined the hypothesis that α-lipoic acid (LA) prevents renal injury in a mouse model of sleep apnea. Methods: Twenty male mice received either intermittent hypoxia (IH) or intermittent air (IA) with or without a LA-enriched diet for 60 days. Plasma and urine samples were collected at the end of study, and kidneys were harvested for protein analysis. Results: Animals in the IH + LA group had lower levels ( p < 0.05) of plasma oxidative stress (8-isoprostane) and inflammation (TNF-α). Renal oxidative stress was also reduced in mice in the IH + LA ( p < 0.05) compared with IH-exposed mice that were fed regular diet. Renal cellular apoptosis and tubular injury were reduced in the IH + LA group. Treatment with LA attenuated IH-induced glomerular hypertrophy and increased albuminuria. Conclusions: Treatment with LA prevents IH-induced renal injury in mice. LA may be a potential therapy for reducing renal dysfunction in patients with OSA. LA can also increase oxidative stress in healthy animals.